2016
DOI: 10.1002/aur.1595
|View full text |Cite
|
Sign up to set email alerts
|

Intact recognition, but attenuated adaptation, for biological motion in youth with autism spectrum disorder

Abstract: Given the ecological importance of biological motion and its relevance to social cognition, considerable effort has been devoted over the past decade to studying biological motion perception in autism. However, previous studies have asked observers to detect or recognize briefly presented human actions placed in isolation, without spatial or temporal context. Research on typical populations has shown the influence of temporal context in biological motion perception: prolonged exposure to one action gives rise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 72 publications
4
46
3
Order By: Relevance
“…Atypicalities in perceptual adaptation have been thought to reflect difficulties of autistic 1 individuals in deriving or using prior knowledge representations accrued from recent sensory experiences (Pellicano and Burr 2012). Within the Bayesian inference, or predictive-coding theoretical frameworks, which, in broad terms, suggest that the brain continually exploits the statistics of the world to predict current sensory input using a hierarchical and bidirectional processing system which aims to minimise prediction error within a cascade of cortical processing (Clark 2013;Friston 2010), adaptation may relate to the atypical encoding of precision in the perceptual hierarchy in autism (Lawson et al 2014) or the inability to process flexibly prediction errors (Van de Cruys et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Atypicalities in perceptual adaptation have been thought to reflect difficulties of autistic 1 individuals in deriving or using prior knowledge representations accrued from recent sensory experiences (Pellicano and Burr 2012). Within the Bayesian inference, or predictive-coding theoretical frameworks, which, in broad terms, suggest that the brain continually exploits the statistics of the world to predict current sensory input using a hierarchical and bidirectional processing system which aims to minimise prediction error within a cascade of cortical processing (Clark 2013;Friston 2010), adaptation may relate to the atypical encoding of precision in the perceptual hierarchy in autism (Lawson et al 2014) or the inability to process flexibly prediction errors (Van de Cruys et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…With regard to social stimuli, attenuated adaptation in autism has been observed consistently within the face-processing domain, including, for example, for facial identity in autistic children (Ewing et al 2013b;Pellicano et al 2007) and relatives of autistic children (Fiorentini et al 2012), for facial configuration (Ewing et al 2013a, b) and eye-gaze direction in children (Pellicano et al 2013) and adults (Lawson et al 2018), and for emotional expressions in children (Rhodes et al 2018) and adults (Rutherford et al 2012). van Boxtel et al (2016 also found that autistic children show reduced adaptation to action discrimination in biological motion (walking vs. running).…”
Section: Introductionmentioning
confidence: 99%
“…There is now considerable evidence for reduced adaptation in autism for high-level visual attributes, both social stimuli (e.g., faces: Pellicano, Jeffery, Burr, & Rhodes, 2007; biological motion: van Boxtel, Dapretto, & Lu, 2016) and nonsocial stimuli (e.g., numerosity: Turi et al, 2015), as well as for other sensory modalities (e.g., touch: Tommerdahl, Tannan, Holden, & Baranek, 2008; audition: Lawson, Aylward, White, & Rees, 2015); audiovisual calibration: Turi, Karaminis, Pellicano, & Burr, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…However, these studies should not be taken to reflect that all perceptual processing of others' actions is intact in autism. Recent evidence suggests that individuals with autism struggle with spatial-temporal integration [van Boxtel et al, 2016] and prediction (von der Lühe et al, 2016), and also when required to segregate motion signals from noise [Manning, Tibber, Charman, Dakin, & Pellicano, 2015]. Therefore, despite sensitivity to the relevant biological kinematic signals within others' actions at a "local" level, autistic individuals may have difficulty processing motion signals with a number of elements due to challenges combining cues-which vary in phase and kinematics-across space into a coherent signal (see also Dakin & Frith, 2005).…”
Section: Discussionmentioning
confidence: 99%